Abdominal imaging. Computational and clinical applications 4th International Workshop, Held in Conjunction with MICCAI 2012, Nice, France, October 1, 2012. Proceedings - Hawkes, David; Vannier, Michael W.; Yoshida, Hiroyuki (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the International Workshop MMCP 2012, held in Nice, France, in October 2012. The book includes 31 papers which were carefully reviewed and selected from 37 submissions. All of the accepted papers were revised by incorporating of the reviewers' comments and re-submitted by the authors to be included in this proceedings volume. The papers are organized into topical sections on colon and other gastrointestinal tract; and liver, kidney, and other organs.